Factors That Affect Exclusive Breastfeeding of Nifas Mothers In Caile Health Center Work Area - Aldina Lestari; Murida Wiryanti; Nabila (Jurnal Life Birth, 2021)
Breast milk is an ideal source of nutrition with a balanced composition and adapted to the needs of the baby's growth. The purpose of this study analyzed the factors of exclusive breastfeeding in mothers in the working region of caile puskesmas. The research method used in this research design uses an analytical design with a cross-sectional approach. The population and sample in this study were 30 respondents using total sampling. The data collection method that is scheduled is a questionnaire sheet. From the researchers obtained the characteristics of respondents seen from the age of most respondents have an age of 20-35 years as many as 28 respondents, and most responded has a high level of elementary education as many as 11 respondents. Univariate analysis data obtained some respondents have fewer years as much as 50.0% and most respondents have a high cultural influence of 70.0% while for health support as well as health while the bivariate analysis using fisher's alternative chi-square statistic test. Result research shows that knowledge levels (p=0.008) and cultural influences (p=0.005) have a significant association with exclusive breastfeeding while health care support (p=1,000) has no relationship with exclusive breastfeeding. The conclusion of this study is that this study can provide information about exclusive breastfeeding of mothers and be input for health workers in the caile health center area and is also useful for all parties and can be a reference for further research